KELEMAHAN PELAKSANAAN PILPRES 2014: SEBUAH ANALISIS - Aryojati Ardipandanto (Sekretariat Jenderal DPR RI, 2015)
This paper discusses the 2014 Presidential Election, in particular its strengths and weaknesses. It is reveals here its main strength lies in its transparency in its process, moreover in public access to information. Some weaknesses connected with the accuracy of voter list, black campaign, and the neutrality of Election Board (KPU), mass media, and quick count institutions. The writer underlined that the problem of the accuracy of voter list can be solved by giving authority to single institution in keeping population data. Meanwhile, black campaign and neutrality of the three different institutions can be overcome by amending Presidential Election Law and strengthening its enforcement.